SYSTEM OF ATTRACTION AND SELECTION OF STAFF FOR LOCAL AUTHORITIES IN UZBEKISTAN (Scientific electronic journal "Labor Economics and Human Capital", 2023)
The article examines the system of attracting and selecting personnel to local governments from a theoretical and practical point of view, based on the analysis of the opinions of domestic and foreign scientists, the recruitment processes in these structures are studied, and the main aspects of the personnel selection process are identified. Also in the study, the situation on attracting and hiring personnel to local government bodies in the conditions of Uzbekistan was studied and proposals were developed for further improvement of this system.
Keywords: local governments, recruitment and hiring system, human resource management.